2015
DOI: 10.5539/gjhs.v8n2p46
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of a Community-Based Health and Nutrition Education on the Management of Diarrhea in an Urban District, Cairo, Egypt

Abstract: Diarrhea is considered as a major cause of mortality in children aged less than five years old. This pre/post interventional study was designed to assess maternal knowledge about diarrhea and implement a community-based health and nutrition education messages. The study was held in Al-Darb Al-Ahamar (ADAA) district, Cairo, Egypt and targeted a random sample of 600 mothers having at least one child under-five years old and complained of at least one previous attack of diarrhea. The study was conducted in three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…The current study showed a significant improvement in the knowledge of participating women after the intervention in areas of food economics, healthy diet, and food safety. This coincides with the findings of other studies [20], [21], [22] where health education interventions had improved the participants’ knowledge significantly.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current study showed a significant improvement in the knowledge of participating women after the intervention in areas of food economics, healthy diet, and food safety. This coincides with the findings of other studies [20], [21], [22] where health education interventions had improved the participants’ knowledge significantly.…”
Section: Discussionsupporting
confidence: 92%
“…The percentage of obesity and overweight among females (5-19 years of age), and even married women (15-49 years) are 36% and 85%, respectively. Also, the rate of anaemia among women in the reproductive age is 25% [4].…”
Section: Introductionmentioning
confidence: 99%
“…Need for support to CHWs in management of child illnesses has been reported from other countries including studies from Peru, South Africa and Uganda (Westgard, Naraine, & Villacorta, 2018;Stellenberg, Van Zyl, & Eygelaar, 2015;Wanduru et al, 2016). Despite inadequate knowledge of CHWs being a frequently reported impediment (Wilford et al, 2018;Fathima et al, 2015;Guenther et al, 2017), CHWs can deliver well under controlled supervised pilot study settings (Abdel-Aziz, Mowafy, & Galal, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Intervention studies focusing on education about how to prevent infant diarrhea were conducted with 600 mothers in Egypt [ 37 ]. Results showed that knowledge of mothers about diarrhea (etiological factors and preventive measures) had improved significantly after the intervention and that health and nutrition education sessions were successful in improving mothers' knowledge regarding preventive measures and management of diarrhea.…”
Section: Discussionmentioning
confidence: 99%